A Care-Based Approach to Transformative Change: Ethically-Informed Practices, Relational Response-Ability & Emotional Awareness. Issue 3 (1st September 2020) - Moriggi, Angela; Soini, Katriina; Franklin, Alex; Roep, Dirk
ABSTRACT: Notions of care for humans and more-than-humans appear at the margins of the sustainability transformations debate. This paper explores the merits of an ethics of care approach to sustainability transformations. It argues that more radical, transformative change can be fostered via three mutually reinforcing dimensions: (a) ethically informed practices; (b) relational response-ability; and (c) emotional awareness. This novel theoretical and methodological lens emphasizes the transformative potential of caring practices and as such extends the reach of the sustainability transformations debate.